Informed health choices intervention to teach primary school children in lowincome countries to assess claims about treatment effects: process evaluation - Nsangi, Allen; Semakula, Daniel; Rosenbaum, Sarah; Nyirazinyoye, Laetitia; Kaseje, Margaret; Sewankambo, Nelson K. (BMJ open, 2019)
We developed the informed health choices (IHC) primary school resources to teach children how to assess the trustworthiness of claims about the effects of treatments. We evaluated these resources in a randomised trial in Uganda. This paper describes the process evaluation that we conducted alongside this trial.To identify factors affecting the implementation, impact and scaling up of the intervention; and potential adverse and beneficial effects of the intervention. All 85 teachers in the 60 schools in the intervention arm of the trial completed a questionnaire after each lesson and at the end of the term. We conducted structured classroom observations at all 60 schools. For interviews and focus groups, we purposively selected six schools. We interviewed district education officers, teachers, head teachers, children and their parents. We used a framework analysis approach to analyse the data.